The effects of feeding low protein and low energy diets with microbial protease supplementation on growth performance, incidence of pododermatitis and immune response in broiler chickens stocked at different densities - Law, Elizabeth Fang Lin (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
A study was conducted to determine the effect of supplementing microbial protease to broiler chickens fed low protein and low energy (LPLE) diets on growth performance (GP), incidence of pododermatitis and antibody production against Newcastle disease (ND) vaccination under two stocking densities. Birds can be fed LPLE starter and low protein-normal energy (LPNE) finisher diet without any adverse effect on growth performance. Protease supplementation was of little benefit to broilers fed diets with lower energy and lower protein. High stocking density (HD) was detrimental to GP and stressful to birds. Low protein diets during the starter period and HD suppressed ND antibody production.